Body mass index and quality of life among the elderly - Kusumaratna, Rina K.; Hidayat, Adi (Universa Medicina, 2009)
Obesity in many countries is a major public health problem. The health problems associated with an increase in the proportion of elderly in the population are further compounded by the increasing prevalence of obesity and overweight in older people. The aimed of this study was to explore any difference of quality of life (QOL) attributable body mass index (BMI) categories using the WHOQOL-BREF instruments. An observational cross-sectional study was conducted in Mampang Prapatan district, South Jakarta. A total of 296 free-living elderly aged 60 years and above were participated in this study. BMI was calculated as the weight (kg) divided by the square of the height (m2). Quality of life was measured by WHOQOL-BREF questionnaire in the Indonesian language version. The results showed that the percentage of overweight subjects was 27.5% in male and 22.2% in female elderly, while the percentage of obese subjects was respectively 8.3 and 13.2.1% respectively. In males, the mean scores on each domain of the QOL were higher compared with females. The significant differences were in social relationship (p=0.000) and environment (p=0018) domains. Among male and female elderly the highest mean scores of each domain of QOL was observed in the environment domain, and mean scores of the environment domain was significantly higher in males compare with females (p=0.018). The results have practical implications for the health of older persons because they show that the overweight have a worse score in two QOL domains, namely psychological health and environment.